Motivasi Sebagai Mediasi Antara Kompetensi Klinis Dan Kepemimpinan Terhadap Kinerja Perawat Di Rumah Sakit Seto Hasbad - Al’adli, Aqdam Fauqo; Pamungkas, Rian Adi; Kusumapradja , Rokiah (Journal of Comprehensive Science, 2025)
This research focuses on the importance of nurses' clinical performance in improving the quality of health care, as well as the role of clinical competence and clinical leadership in driving motivation to achieve optimal performance. Hospitals are faced with challenges in developing technical competencies, strengthening leadership, and increasing nurse motivation. This study aims to analyze the influence of clinical competence and clinical leadership on nurses' clinical performance, with motivation as a mediating variable at Seto Hasbadi Hospital, Bekasi. The method used was a quantitative analysis with a cross-sectional design. The sample consisted of 100 nurses selected using the Slovin formula and purposive sampling techniques. Data was collected through a questionnaire with a 5-point Likert scale and analyzed using Structural Equation Modeling (SEM) with the SEM-PLS application. The results of the study show that clinical competence and clinical leadership have a significant effect on the clinical performance of nurses, both directly and through motivation. Clinical competence has the greatest influence, with motivation mediating the relationship between these variables. The implication of this research is the importance of hospital management in developing training that improves nurse competence, strengthens leadership, and manages motivation through incentives and a supportive work environment to improve nurses' clinical performance in health services